CORELATON OF DIETARY HABIT WITH HYPERTENSION IN TRIMESTER III PREGNANT WOMEN AT PUSKESMAS BATU AJI, BATAM CITY - Yani Christina; Meirina Daulay (Universitas Batam, 2020)
Background : Hypertension is a dangerous disease, especially if it occurs in women who are pregnant. hypertension increases mortality and morbidity in pregnant women. According to the Inter-census Survey Data (SUPAS) in 2015, the maternal mortality rate was recorded at 305 per 100,000 live births, which was caused by hypertension at 13% (Indonesia KKR, 2017). The purpose of this study was to determine the relationship between diet and the incidence of hypertension in third trimester pregnant women. Method : The research method used was an analytic survey with a cross sectional approach. Conducted at Puskesmas Batu Aji, Batam City, the study was conducted for 6 months, the population in this study were 206 pregnant women in the third trimester, with a sample of 67 respondents, using the Porposive sampling technique. Data collection using a questionnaire. Data presented in tabular and textual form, data analysis using Chi-square. Result : The results of the study of 67 pregnant women in the third trimester, found that 45 respondents had hypertension, there were 59 respondents or (73.1%) with poor diet. From the Chi-Square test with a limit of significance (Î±) = 0.05 and the result of p-value = 0.000 which means p-velue <(Î±), it is said that the two variables have a relationship or Ha is accepted, this means that there is a relationship between eating patterns and events. Conclusion : Hypertension in Trimester III Pregnant Women at Batu Aji Health Center. Suggestions so that respondents and readers can apply a good diet that is obtained in everyday life.